Kreativitas Seniman Tingkilan Kutai Kalimantan Timur - Irawati, Eli (PANGGUNG, 2013)
ABSTRACTÃÂ For Kutai society, the term of Tingkilan has two meanings: first, as a betingkilan activity, that is performed by the performers through chanting the songs, whereas the lyrics are in the form of pantun which are intended as satire. Second, betingkilan is also known as a kind of musical ensemble. ÃÂ The creativity of Tingkilan playings are inseparable from some aspects that influenced it, either external or internal factors. The external aspects are connected with the Kutai societyÃ¢â¬â¢s views about their concepts of life, customs, and traditions, due to geographical situations, history, and the advance of science and technology. ÃÂ Whereas the internal aspects that influence the improvement of Tingkilan playings are the eÃ¯Â¬â¬orts of the artists themselves to create new works productively that can accommo- date the contemporary Kutai societyÃ¢â¬â¢s preferences which of course need the artists creative touch.ÃÂ Keywords: Creativity aspects, Tingkilan, Kutai, and ethnomusicologyÃÂ ÃÂ ABSTRAKÃÂ Tingkilan dalam masyarakat Kutai memiliki dua pengertian yaitu sebagai sebuah ak- tivitas betingkilan atau mendendangkan lagu yang berisi sindiran lewat pantun dan juga untuk penyebutan sebuah ansambel musik. Kreativitas Tingkilan tidak terlepas dari bebe- rapa faktor yang mempengaruhinya baik yang disebabkan oleh faktor eksternal maupun faktor internal. Faktor eksternal yang secara tidak langsung dapat mempengaruhi pan- dangan masyarakat tentang konsep hidup, adat, dan tradisi masyarakat Kutai disebabkan oleh letak geografis yang strategis, sejarah, dan kemajuan di bidang ilmu pengetahuan dan teknologi. Adapun faktor internal yang mempengaruhi perkembangan Tingkilan adalah adanya upaya dari para senimannya untuk produktif menciptakan karya-karya baru yang bisa mengakomodir dari selera masyarakat Kutai zaman sekarang yang tentunya membu- tuhkan sentuhan olah kreativitas dari para senimannya.ÃÂ Kata kunci: Faktor-faktor kreativitas, Tingkilan, Kutai, dan etnomusikologi